Effect of Pre PCI Antiplatelet Therapy in STEMI Patients Undergoing Primary PCI - Khan, Muhammad Idrees; Parvez, Muzdalfa; Zada, Akhtar; Amjad, Shamas; Muhammad Hafeez; Yar, Ahmad (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the effectiveness and safety of pre-percutaneous coronary intervention (PCI) antiplatelet therapy in patients with ST-elevation myocardial infarction (STEMI) undergoing primary PCI, specifically focusing on ST-segment resolution, mortality, and bleeding outcomes. Methodology: A prospective, randomized clinical trial was conducted from January 2023 to December 2023 at Hayatabad Medical Complex, Peshawar, Pakistan. A total of 300 STEMI patients were randomized into two groups: one received pre-PCI antiplatelet therapy, while the control group received standard post-PCI therapy. Outcomes assessed included ST-segment resolution, 30-day mortality, and bleeding events. Statistical analysis was performed using chi-square tests and t-tests to determine differences in outcomes between groups, with significance set at p<0.05. Results: Patients receiving pre-PCI antiplatelet therapy demonstrated a higher rate of ST-segment resolution (74.7%) compared to the control group (71.3%), though this difference was not statistically significant (p=0.603). A non-significant trend toward lower 30-day mortality was observed in the pre-PCI group (11.3% vs. 12.7%, p=0.859). Bleeding events were comparable between groups, with no significant increase in the pre-PCI therapy group (p=0.286). Conclusion: Pre-PCI antiplatelet therapy shows promise in improving reperfusion outcomes without elevating bleeding risk in STEMI patients, suggesting it could be a valuable addition to standard care in similar clinical settings.